Physiological asymmetry in uterine artery blood flow during the first trimester of pregnancy: New insights from a quantitative assessment using Pulsed-wave color Doppler and M-mode color power angio imaging. (April 2022) - Leible, Sergio; Canals, Andrea; Sepulveda, Waldo
Abstract: Introduction: This study aimed to quantify uterine artery (UtA) blood flow and its hemodynamic components throughout the first trimester of pregnancy using Doppler ultrasound. Methods: Cross-sectional cohort study involving women undergoing a routine ultrasound scan between 5 and 13 weeks' gestation. UtA blood flow was measured using Pulsed-wave Color Doppler to assess blood flow velocity across the cardiac cycle and M-mode Color Power Angio imaging to assess UtA diameter. A formula was applied to calculate systolic and diastolic blood flow volumes according to Poiseuille's equation. Results: A total of 330 women with a single viable first-trimester pregnancy agreed to participate in this study. A stepwise increase in total UtA blood flow was observed during the first trimester, with significant increases at 7, 8, and 11 weeks. No significant differences in blood flow were observed between right and left UtAs. However, there was a statistically significant difference when comparing the UtA based on higher and lower blood flow, with a mean ± SD of 64.4% ± 10.5% through the former ( p  < 0.001). The increase in the UtA blood flow was secondary to an increase in the blood flow rate between 5 and 10 weeks. A significant increase in UtA diameter was only identified from 11 weeks onwards. Discussion: UtA blood flow in the first trimester is asymmetrical, at a constant ratio of ≈2:1. An interpretive model of the possible origin of this pattern during early pregnancy is proposed. Highlights: Uterine artery blood flow during pregnancy can be quantified noninvasively. This blood flow in early human pregnancy is asymmetric at a constant ratio of ≈2:1. There were significant increases of blood flow at 7, 8, and 11 weeks. A significant increase in arterial diameter was only identified from 11 weeks.